Q as Hypothesis: A Study in Methodology - Watson, Francis (New Testament studies, 2009)
Arguments for the Q hypothesis have changed little since B. H. Streeter. The purpose of this article is not to advocate an alternative hypothesis but to argue that, if the Q hypothesis is to be sustained, the unlikelihood of Luke's dependence on Matthew must be demonstrated by a systematic and comprehensive reconstruction of the redactional procedures entailed in the two hypotheses. The Q hypothesis will have been verified if (and only if) it generates a more plausible account of the Matthean and Lukan redaction of Mark and Q than the corresponding account of Luke's use of Mark and Matthew.